Developmental Pathways of Male Morphotypes of Macrobrachium rosenbergii in Natural Habitat - B., Madhusoodana Kurup; M., Harikrishnan (Fishery Technology, 2025)
The probable transformation pathways of male morphotypes in natural habitat were investigated using the distance function analysis and size characterization of morphotypes. The relative distance between different male morphotypes suggested the possibility of transformation of morphotypes following three developmental pathways. The normal pathway was SM -WOC -SOC -t-SOC -WBC -SBC -OBC, while the two bypass transformation pathways were SM -WOC -WBC -SBC -OBC and SM -WOC -t-SOC -WBC -SBC -OBC. The mechanism underlying transformation of morphotypes following normal and bypass developmental pathways is discussed.